A public-private partnership for malaria control: lessons from the Malarone Donation Programme - Oyediran A.B.O. Olukayode; Ddumba Edward M.; Ochola Samuel A.; Lucas Adetokunbo O.; Koporc Kim; Dowdle Walter R. (The World Health Organization, 2002)
In 1996, Glaxo Wellcome offered to donate up to a million treatment courses annually of Malarone, a new antimalarial, with a view to reducing the global burden of malaria. The Malarone Donation Programme (MDP) was established the following year. Eight pilot sites were selected in Kenya and Uganda to develop and evaluate an effective, locally sustainable donation strategy that ensured controlled and appropriate use of Malarone. The pilot programme targeted individuals who had acute uncomplicated Plasmodium falciparum malaria that had not responded to first-line treatments with chloroquine or sulfadoxine-pyrimethamine. Of the 161 079 patients clinically diagnosed at the pilot sites as having malaria, 1101 (0.68%) met all the conditions for participation and received directly observed treatment with Malarone. MDP had a positive effect at the pilot sites by improving the diagnosis and management of malaria. However, the provision of Malarone as a second-line drug at the district hospital level was not an efficient and effective use of resources. The number of deaths among children and adults ineligible for MDP at the pilot sites suggested that high priority should be given to meeting the challenges of malaria treatment at the community level.